RELIGIOSITY IN SALAWAT DEDAUNAN SHORT STORY - Rahim, Yuliadi Muh (Widyariset, 2013)
This research is conducted to reveal the value of religiosity in Salawat Dedaunan short story. This religiosity value would be revealed through the depiction of characters in the story and dialogue. The theory used in this study is the religiosity theory proposed by Glock and Stark. The method used in this research is qualitative descriptive method whilst data collection uses literary technique. The results obtained in this study is Salawat Dedaunan short story embodies religious value, such as the dimensions of ritual engagement, ideological engagement, intellectual engagement, experiential involvement and consequential involvement.